Facile synthesis of a micro-scale MOF host–guest with long-lasting phosphorescence and enhanced optoelectronic performance. Issue 74 (28th August 2019) - Yang, Xiao-Gang; Lu, Xiao-Min; Zhai, Zhi-Min; Zhao, Ying; Liu, Xin-Yi; Ma, Lu-Fang; Zang, Shuang-Quan
Abstract : Micro-scale MOF host–guest with tunable phosphorescence and enhanced optoelectronic performance can be obtained by a facile and scalable precipitation process in aqueous solution. Abstract : Micro-scale MOFs with a persistent phosphorescence lifetime of 900 ms can be facilely synthesized by a fast precipitation process in aqueous solution. The in situ encapsulation of a dye into the MOF matrix can expressly tune the phosphorescence color from green to a rare example of red emission with a lifetime of 450 ms, highly enhancing the photoelectrocatalytic water splitting.